The relationship between high-sensitivity C-reactive protein and gallstones: a cross-sectional analysis - Jiang, Zhimeng; Jiang, Huixin; Zhu, Xingyu; Zhao, Donglin; Su, Feifei (Frontiers in Medicine, 2024)
Background and Objective: High-sensitivity C-reactive protein (hs-CRP), a classical indicator of inflammation, holds significant clinical value in various diseases.The relationship between hs-CRP and gallstones, however, remains poorly studied at present. The relationship between hs-CRP and gallstones will be investigated in this study.Methods: Data from the 2017-2020 National Health and Nutrition Examination Survey (NHANES) were analyzed, focusing on participants aged 20 years and older who provided complete hs-CRP and gallstone information. Due to the skewed distribution of hs-CRP, the data were log-transformed (Log (hs-CRP)) to achieve normalization. Logistic regression analysis, subgroup analysis, and smoothed fitted curves were applied to determine the relationship between Log (hs-CRP) and the presence of gallstones.The study included 4,484 participants with an average Log (hs-CRP) of 1.18 ± 0.74. The prevalence of gallstones was 11.15%, increasing with higher Log (hs-CRP) levels (quartile 1: 8.31%; quartile 2: 8.76%; quartile 3: 11.98%; quartile 4: 16.36%; p < 0.0001). Adjusting for all covariates in Model 3, each 10-fold increase in hs-CRP (corresponding to a one-unit increase in log10(hs-CRP)) corresponded to a 29% increased odds of gallstones prevalence [1.29 (1.12-1.49)]. The smoothed fitted curve showed a positive linear relationship between Log (hs-CRP) and gallstones prevalence. The results of subgroup analyses exhibited a more pronounced positive correlation in the 20-40 age group [1.70 (1.33, 2.16)], compared to those aged 40-60 years [1.22 (1.01, 1.48)] and 60-80 years [1.14 (0.98, 1.34)].Higher Log (hs-CRP) levels are linked to a greater prevalence of gallstones. We still need to carry out further large prospective research to explore the causal relationship of this association.